Ecologia pesqueira do alto rio Paraná. - Costa, Rodrigo Silva da (2007)
This study was developed aiming at expanding knowledge regarding the negative effects of dams installed in the upper Paraná River on the fishing, especially in downstream portion of the Porto Primavera dam, in terms of the fish catch composition and fisheries yield of the most important fish species landed and socioeconomic aspects of fishermen operating in the study region. catch composition and biomass (kg*day-1) and fishing effort (fisher*day-1) data were analyzed. This data set was obtained through the database of the artisanal fisheries monitoring program developed by Núcleo de Pesquisas em Limnologia, Ictiologia e Aquicultura (Nupélia) State University of Maringá around of Guaíra (PR) town, consisting of information regarding the period prior to the closure of Porto Primavera dam (1987-1997) and after it starts operate (1998-2005). The data for characterization of the fishing infrastructure and socioeconomic status of fishermen have been collected through personal interviews conducted in 2004 in visits to riverine locations between downstream Porto Primavera Dam and Guaira town (PR). This work was divided into two chapters. The first chapter, entitled "Temporal variation in the composition and yield of artisanal fisheries of the upper Paraná River, PR - Brazil: the chronic effects of impoundments" revealed that buses present in the river, especially the Porto Primavera dam, promoted a significant change in specific composition, with major contribution of species independent of the hydrological cycle and low market value, and fisheries yield, especially on migratory fish species that has high commercial value. The second chapter, entitled "The structure and socio-economic aspects of small-scale fishing developed in the upper Paraná River, between Porto Primavera Dam and Itaipu Reservoir" showed the existence of a heterogeneous spatial pattern in fisheries infrastructure and socioeconomic status of fishermen in the region studied.